2016
DOI: 10.1016/j.jsxm.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Cyproterone Acetate vs Spironolactone on Serum High-Density Lipoprotein and Prolactin Concentrations in the Hormonal Treatment of Transgender Women

Abstract: Introduction Spironolactone and cyproterone acetate (CPA) are the two main antiandrogen medications used in feminizing hormone therapy in transgender women. Previous studies have suggested that these two agents might have opposite effects on high-density lipoprotein (HDL) level when used in this context, and limited data have suggested CPA increases prolactin more than spironolactone. Aim To compare the effects of spironolact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Cyproterone acetate is not available in the United States or Japan. Subtle differences in spironolactone and CPA effects on lipids and prolactin levels may result in the endocrinologist's choosing one over the other for the individual patient . Progestin agents when used alone at higher doses than for contraception, such as for dysfunctional uterine bleeding, are also associated with increased VTE risk but are not frequently used in the transgender population.…”
Section: Case I: Mtfmentioning
confidence: 99%
“…Cyproterone acetate is not available in the United States or Japan. Subtle differences in spironolactone and CPA effects on lipids and prolactin levels may result in the endocrinologist's choosing one over the other for the individual patient . Progestin agents when used alone at higher doses than for contraception, such as for dysfunctional uterine bleeding, are also associated with increased VTE risk but are not frequently used in the transgender population.…”
Section: Case I: Mtfmentioning
confidence: 99%
“…Defreyne and colleagues 195 revealed that CPA increased prolactin levels in TW but the levels decreased when TW discontinued CPA. Fung and colleagues 117 demonstrated higher prolactin levels in TW receiving CPA than those taking spironolactone. Given these newer data, we recommend checking prolactin only in those patients with signs or symptoms of hyperprolactinaemia before or after starting feminizing GAHT.…”
Section: Part 4: Other Health Considerations For Twmentioning
confidence: 96%
“…In contrast, other markers suggest a decreased risk compared with reference men and women as well as trans men [e.g. less insulin resistance, 34,39,113,115,118 decreasing/stable blood pressure, 116,118,119 decreasing LDL 34,115,117,118 and smaller waist-to-hip ratio (WHR) 122 ]. Some conflicting results can be explained by the older mean age of TW compared with trans men, geographical location, GAHT regimen, minority stress (e.g.…”
Section: Part 3: Risks Associated With Gahtmentioning
confidence: 99%
“…The addition of the anti-androgen cyproterone acetate (or other agents) to the HT of trans women makes it difficult to isolate effects driven by estrogen, consequent to testosterone suppression or to specific side-effects of the anti-androgen. Indeed, HDL-C concentrations are reduced in trans women treated with cyproterone acetate, whereas they increase with other anti-androgens (e.g., spironolactone or a GnRH-analog) 46,47 . In our study the decreased HDL-CEC in trans women is likely to be attributed to the use of cyproterone acetate; which, aside from the anti-androgen activity also exert progestogen-like effects.…”
Section: Cholesterol Efflux Capacity and Sex Hormonesmentioning
confidence: 99%